The management of the process of forming university students’ tolerance in the conditions of digitalization of higher education - Konstantinovna Oreshkina, Anna (2021)
The article deals with the formation of students’ tolerance and management of this process. The aim of the article is to cover theoretical and empirical aspects of the management of students’ tolerance formation. A special focus is made on the role of tolerance in modern society and for the educational system as well as on the contradictions which determine the relevance of tolerance in the university environment. Tolerance is a complex, multifaceted phenomenon which touches all aspects of student life. Entering the university, young people find themselves surrounded by many different personalities who have their own values and beliefs in life. This calls for the necessity to respect and accept a different opinion and a different way of life. Therefore, nowadays the formation of tolerance acquires special importance in educational institutions as it is tolerance which is the basis of effective communication in a politically cultural society like the Russian Federation. So the formation of tolerance is a social order as it is impossible to develop the educational system unless this aspect is included. We scrutinized relevant literature on the issue and came to the conclusion that the formation of tolerance can be only achieved by means of democratic management and students’ conscious choice of tolerant attitudes and behavior, which excludes any pressure or foisting. The study involved the choice of methods and an algorithm, which comprised the diagnosis of the mentioned parameters, conducting a formative experiment, repeated check of the parameters and performing a statistic analysis of the results. The study was carried out on the base of the Institute of Foreign languages, RUDN University (Russia). The research results allow drawing a conclusion about high effectiveness of the implemented actions aimed at the formation of students’ tolerance.